Green Tourism-Based CSR as Practiced By Melasti Beach Management - Ni Wayan Agustini; I Ketut Budarma; I Made Darma Oka; Cokorda Istri Putra Widhari; I Putu Krisna Arta Widana (International Journal of Travel, Hospitality and Events, 2023)
Purpose: This study aims to analyze the implementation of green tourism-based CSR (corporate social responsibility) by the regional head of Melasti Beach management, Badung, Indonesia. Research methods: The data collection methods used are observation, interviews, document study, and focus group discussions. Furthermore, data analysis used descriptive qualitative analysis, including data reduction, presentation, and conclusion. Results and discussion: The results show that CSR activities of the Ungasan Bupda (Baga et al.) in managing Melasti Beach include four aspects, namely economic aspects, social aspects, cultural aspects, and environmental aspects. Implication: All CSR activities carried out reflect the theory of sustainable tourism by paying attention to economic, social, cultural, and environmental sustainability.   Keywords: corporate social responsibility, green and sustainable tourism, beach.